1988
DOI: 10.1139/f88-226
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Feeding Responses of Male versus Female Yellow Perch (Perca flavescens) Treated with Estradiol-17β

Abstract: In yellow perch (Perca flavescens) (initially 13–16 g total weight) fed to satiation (3.0–3.5% of body weight per day), estradiol-17β (E2) at 15 μg/g diet stimulated weight gain and food consumption of both sexes but did not influence food conversion efficiency (FCE), as measured by weight gain of fish per weight of food consumed. Females fed to satiation gained more weight, consumed more food, and had higher FCE than males. In perch fed a restricted ration (1.2% of body weight per day), the differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 10 publications
12
55
1
Order By: Relevance
“…The absence of significant sexrelated effect on the growth of Eurasian perch is in agreement with previous studies on the American yellow perch (Malison et al 1988) and the Eurasian perch (Babiak et al 2004). Stejskal et al (2009) found that the significance differences in body weight between all-female and mixedsex stocks of perch began at age 144 days, when fish were over 13 g. The sexual growth dimorphism in perch probably appears markedly when sexual maturation reduces somatic growth.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of significant sexrelated effect on the growth of Eurasian perch is in agreement with previous studies on the American yellow perch (Malison et al 1988) and the Eurasian perch (Babiak et al 2004). Stejskal et al (2009) found that the significance differences in body weight between all-female and mixedsex stocks of perch began at age 144 days, when fish were over 13 g. The sexual growth dimorphism in perch probably appears markedly when sexual maturation reduces somatic growth.…”
Section: Discussionsupporting
confidence: 92%
“…Effects on growth of female gonadal hormones have rarely been tested in squamate reptiles (but see Lerner and Mason, 2001) [for evidence in other vertebrates, see Malison et al (Malison et al, 1988) or Govoni et al (Govoni et al, 2008)], which precludes evaluating whether estrogens or progestins may affect female growth in the opposite direction in female-versus male-larger lizard species [see Cutler (Cutler, 1997) for support for the role of low levels of estrogens in regulation of growth in humans]. Testing this hypothesis will require further experimental work focused specifically on hormonal manipulations in females of male-larger and female-larger species.…”
Section: Discussionmentioning
confidence: 99%
“…Factors influencing sexual dimorphism have been investigated for a closely related percid, yellow perch, in which estrogenic compounds stimulate female growth, whereas androgenic compounds retard male growth rates (Malison et al 1985(Malison et al , 1988. For both sexes, these changes in growth rate were related to maturation.…”
Section: Characterizing Simulated Walleye Populationsmentioning
confidence: 99%